Formulation and Evaluation of Nanogel from Tubifex Worms (Tubifex sp.) as a Future Therapeutic Agent for Burn Wounds - Aminah Syarifuddin; Cucu Arum Dwi Cahya (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Burns are one of the most common types of injuries found in the community. Burn treatment tends to be relatively expensive, which often leads to suboptimal care and prolonged healing time. Therefore, innovation in pharmaceutical formulations that are more effective, affordable, and based on natural ingredients is needed. One of the widely used dosage forms is semisolid gel, as it is practical, non-sticky, and comfortable to use. Currently, nanogel development has attracted significant attention because it can enhance the absorption of active compounds, provide more controlled drug release, and reduce toxicity. Indonesia, with its rich biodiversity, has great potential for the exploration of natural materials, including the aquatic worm Tubifex sp. Objective: This study aimed to formulate and evaluate Tubifex sp.-based nanogel as a therapeutic agent for burn wounds. Methods: The study employed an experimental method, including physical stability tests of the nanogel and in vivo tests on male white rats with controlled burn injuries. Results: The results showed that all treatment groups experienced progressive wound diameter reduction over 14 days. The negative control showed only 36.6% healing, while the positive control reached 90%. The Tubifex sp. nanogel demonstrated promising results, with formula F1 (3.75%) and F2 (7.5%) achieving 80–86.6% healing, while formula F3 (15%) reached 93.3%, even surpassing the positive control. The effectiveness of the nanogel is believed to be related to the protein, collagen, and antioxidant content in Tubifex sp., which play important roles in tissue regeneration.Conclusion: Tubifex sp. nanogel has the potential to become an innovative, natural-based therapy for burn treatment in the future.